Characterizing Maize Hybrid Varieties in Lamjung, Nepal: A Study on Varietal Traits - Pankaj Kumar Yadav; Pappu Kumar Sah; Prabina Bhujel; Ankit Ojha (International Journal of Agronomy)
The study evaluated the performance of 10 hybrid maize varieties during the spring season of 2022 using a randomized complete block design. The results showed that RML145/RL197 had the highest plant germination percentage, while Rampur Hybrid-12 had the highest plant height and leaf area index. Phenological traits were significantly earlier in PVAEQH-1, and the silking–tasseling interval was the shortest in Rampur Hybrid-14. Yield-attributing characteristics varied, with Rampur Hybrid-10 and PVAEQH-1 having the longest cob lengths and largest cob diameters. The number of rows per cob was higher in Rampur Hybrid-16 and CML491/CLWQHZN51, while the number of kernels per row was higher in CML491/CLWQHZN51 and RML83/RML146. CAH1511 had the highest thousand grain weight, followed by Rampur Hybrid-10. RML145/RL197 and RML83/RML146 were identified as high-yielding varieties, suggesting further multilocational and multiyear trials to confirm these findings and recommend these varieties to farmers in midhill regions, particularly in Lamjung.